EXAMINING THE IMPACT OF PHYSICAL EDUCATION CURRICULUM ON SCHOOL FITNESS INSTRUCTION - Sumal, Ravinder; Singh, Kanwaljeet (International Journal of Psychosocial Rehabilitation, 2021)
Increasing one's participation in physical education, physical exercise, or a sport has been shown in well-conducted longitudinal studies to preserve or even improve one's academic performance. When physical education, physical exercise, or sports take up a significant percentage of class time (up to an additional hour per day), students appear to learn more quickly per unit of classroom time. Physical activity has been linked to improved cognitive performance in children, especially those in elementary and middle school. While all three of these abilities are enhanced by physical activity, perceptual skills appear to be the most affected.